Characterization of personal health determinants in a sample of adolescents from Hidalgo - Zaragoza-Cortes, Jessica; Menchaca-Armenta , Imelda; Miranda Lara, Victor Ramón; Zamora-Cerritos, Karen; León-Rivera, Jesús Ernesto; García-González, Alejandra; Flores-Valencia, Margarita Esthela (Mexican Journal of Medical Research ICSA, 2025)
Introduction: Personal health determinants are recognized as important modifiable risk factors of chronic diseases. Objective: Characterize personal health determinants in a sample of adolescents. Methods: This descriptive, cross-sectional, retrospective study used the state databases of the Health Determinants and Healthy Lifestyle Monitoring Questionnaire from the 17 jurisdictions in Hidalgo, México 2020, with 66 items, 4 sections: Demographic information, health perception, and risk factors; perception of eating behavior; perception of physical activity behavior, weight, and height. Selection criteria were complete, the final sample consisted of n=687. Statistical analysis: The chi-square test was used, and odds ratio with a 95% confidence interval. Results: There were 69% women and 31% men (16.7 ± 1.6 years); 7.6% had short stature, 27.1% were possibly overweight, 11.2% overweight, and 0.7% were obese. The adolescents from 17-19 years were 3 (95% CI 1.90, 4.78) times more likely to smoke tobacco. By sex, men were 1.5 (95% CI 1.02, 2.34), and were 2 (95% CI 1.19, 3.39) times more likely to have smoked e-cigarettes. Those between 17-19 years were 4.5 (95% CI 3.29, 6.26) times more likely to have their blood pressure measured, 3.5 (95% CI 2.52, 4.94) times their glucose measured, and 2.0 (95% CI 1.39, 3.10) times their lipids measured. Regarding exercise, 61.1% performed physical activity <30 min/day and 66.5% sat for >2 hours. Men were 1.9 times more likely to engage in physical activity ≥3 times/week (95% CI 1.32, 2.72) and 1.8 times (95% CI 1.11, 2.97) to engage in ≥30 minutes/day; 66.2% reported consuming 1-2 glasses of sugary drinks daily. Conclusions: We found a high risk of overweight, cardiometabolic risk factors, physical activity, and consumption of sugary drinks and tobacco, with significant differences by sex and age.